Phylogenetic analysis among 27 Chinese populations and genetic polymorphisms of 20 autosomal STR loci in a Chinese Uyghur ethnic minority group. Issue 5 (3rd September 2018) - He, Guang-Lin; Chen, Peng-Yu; Gao, Bo; Han, Yan-Yan; Zou, Xing; Song, Feng; Yan, Jing; Hou, Yi-Ping
Abstract: Allele frequency data and forensic statistical parameters were determined for 20 autosomal short tandem repeat (STR) loci of the PowerPlex 21 System in 214 unrelated healthy individuals of a Uyghur ethnic minority group living in Xinjiang province, northwest China. A total of 232 alleles were observed with the corresponding allele frequencies ranging from 0.0023 to 0.5304. All loci were consistent with Hardy–Weinberg equilibrium (HWE) after the Bonferroni correction ( p  > 0.0025). The combined probability of exclusion, power of discrimination, probability of matching value were 0.999999999, 0.9999999999999999999999995, and 4.78246 × 10 −25, respectively. Our results revealed that the 20 STRs were highly polymorphic and informative, and could be suitable for forensic application, especially parentage test and personal identification. The further population comparison between the Uyghur and other 26 reference populations revealed that the loci of D13S317, TH01 and D6S1043 showed high ethnical specificity. Phylogenetic analysis based on 19 shared loci demonstrated that the Uyghur had a close genetic relationship with the Kazakh, but a distinct genetic distance with other Chinese populations from different ethnicity and regions.